Pengaruh Variasi Massa Serat Pada Green Composite Serat Daun Nanas dan Sari Pati Kentang Terhadap Kekuatan Tarik dan Densitas - Prayudha, Komang Dicky Ari; Kencanawati, Cok Istri Putri Kusuma; Astawa, Ketut (Teknik Desain Mekanika, 2024)
Abstract The advancement of science and technology in the industrial world has resulted in an increasing demand for green composite materials. Green composite materials were developed to reduce the use of materials that are unfriendly and harmful to the environment. It is necessary to create an innovation in the development of environmentally friendly composites by combining natural-based matrices and fibers. This research uses a natural matrix, namely potato starch juice combined with 1 cm pineapple leaf fiber with a mass variation of 95%: 5%, 90% : 10%, 85% : 15%. In the process of making the matrix, the potato starch juice was heated to a hot temperature of 170oC on a 200 rpm magnetic stirrer, then molded using acrylic molds and made by hand lay-up method. The dimensions of the tensile test specimens follow ASTM D3039 and the dimensions of the density test specimens follow ASTM D792-08. The highest tensile strength test results in the variation of 15% fiber mass fraction obtained tensile stress 4.210 MPa, strain 0.687% and elastic modulus 0.616 GPa, while the lowest tensile strength in the variation of 5% fiber mass fraction with tensile stress 1.543 MPa, strain 0.623% and elastic modulus 0.359 GPa. The highest density test results were obtained in the 5% fiber mass fraction variation of 1.646 gr/cm3. While the lowest density value is obtained in the variation of 15% fiber mass fraction of 1.581 gr/cm3. Keywords: Bioplastic, Green Composite, Potato Starch, Pineapple Fiber, Mass Fraction, Tensile Test, Density Test